2006
DOI: 10.1177/104063870601800304
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Multiwell Colorimetric Assay for Measuring Neutrophil Chemoattractant Activity in Bronchoalveolar Lavage Fluid of Horses with Recurrent Airway Obstruction

Abstract: Abstract. The criteria used to diagnose recurrent airway obstruction (RAO) in affected horses include demonstration of reversible lower airway obstruction and greater than 25% neutrophils in bronchoalveolar lavage fluid (BALF). Additional objective laboratory tests are needed to improve diagnostic accuracy and to monitor response to treatment. The goal of this study was to determine if neutrophil chemoattractant activity of BALF could be measured by using a previously described, rapid, multiwell colorimetric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…TNF‐α induces an increase in the expression of the adhesion molecule ICAM‐1 in both human endothelial and bronchial epithelial cells in vitro, which may foster local neutrophil influx in vivo . Given the nature and concentration of the molecules detected in BALF from heaves‐affected horses, it is not surprising that our experiments, in agreement with previous reports, showed an increased migration of neutrophils toward BALF from heaves‐affected horses compared with healthy horses.…”
Section: Discussionsupporting
confidence: 91%
“…TNF‐α induces an increase in the expression of the adhesion molecule ICAM‐1 in both human endothelial and bronchial epithelial cells in vitro, which may foster local neutrophil influx in vivo . Given the nature and concentration of the molecules detected in BALF from heaves‐affected horses, it is not surprising that our experiments, in agreement with previous reports, showed an increased migration of neutrophils toward BALF from heaves‐affected horses compared with healthy horses.…”
Section: Discussionsupporting
confidence: 91%
“…Since despite much effort receptors for SCGB 1A1 have not been conclusively identified and the mechanisms for chemotaxis inhibition remain elusive. Hall and colleagues [44] reported that BAL fluid from RAO-affected animals enhanced chemotaxis. However, BAL fluid contains many mediators produced by bronchial epithelium or leaked into the airways from vasculature, and such assay does not allow dissection of individual protein effects.…”
Section: Discussionmentioning
confidence: 99%